Draft Genomes of Amaranthus tuberculatus, Amaranthus hybridus, and Amaranthus palmeri. (24th August 2020) - Montgomery, Jacob S; Giacomini, Darci; Waithaka, Bridgit; Lanz, Christa; Murphy, Brent P; Campe, Ruth; Lerchl, Jens; Landes, Andreas; Gatzmann, Fanny; Janssen, Antoine; Antonise, Rudie; Patterson, Eric; et al.
Abstract: Amaranthus tuberculatus, Amaranthus hybridus, and Amaranthus palmeri are agronomically important weed species. Here, we present the most contiguous draft assemblies of these three species to date. We utilized a combination of Pacific Biosciences long-read sequencing and chromatin contact mapping information to assemble and order sequences of A. palmeri to near-chromosome-level resolution, with scaffold N50 of 20.1 Mb. To resolve the issues of heterozygosity and coassembly of alleles in diploid species, we adapted the trio binning approach to produce haplotype assemblies of A. tuberculatus and A. hybridus . This approach resulted in an improved assembly of A. tuberculatus, and the first genome assembly for A. hybridus, with contig N50s of 2.58 and 2.26 Mb, respectively. Species-specific transcriptomes and information from related species were used to predict transcripts within each assembly. Syntenic comparisons of these species and Amaranthus hypochondriacus identified sites of genomic rearrangement, including duplication and translocation, whereas genetic map construction within A. tuberculatus highlighted the need for further ordering of the A. hybridus and A. tuberculatus contigs. These multiple reference genomes will accelerate genomic studies in these species to further our understanding of weedy evolution within Amaranthus .